Crossodactylodinae Fouquet, Blotto, Maronna, Verdade, Juncá, de Sá & Trefaut Rodrigues, 2013 is an invalid junior synonym of Paratelmatobiinae Ohler & Dubois, 2012 (Amphibia, Anura) - Dubois, Alain (Zootaxa, 2013)
Among the results of their survey of the phylogenetic relationships among over 2800 species of recent amphibians, Pyron & Wiens (2011) identified a new clade of frogs including the genera Paratelmatobius Lutz & Carvalho, 1958 and Scythrophrys Lynch, 1971. Both these genera were previously placed in the family Leptodactylidae Werner 1896 (1838), whether conceived as a large (e.g., Frost et al. 2006) or a more restricted family (e.g., Grant et al. 2006). Pyron & Wiens (2011) erected a subfamily “Paratelmatobiinae” for these two genera. Unfortunately, as they provided no diagnostic character for this new taxon, their nomen is a nomen nudum. Ohler & Dubois (2012) pointed this out and provided a diagnosis, thus making the nomen Paratelmatobiinae available.